A sweet spot for highly efficient growth of vertically aligned single-walled carbon nanotube forests enabling their unique structures and properties. Issue 1 (1st December 2015) - Chen, Guohai; Davis, Robert C.; Futaba, Don N.; Sakurai, Shunsuke; Kobashi, Kazufumi; Yumura, Motoo; Hata, Kenji
Abstract : We report the existence of a SWCNT "sweet spot" in the CNT diameter and spacing domain for highly efficient synthesis, within which SWCNTs possessed a unique set of characteristics. Abstract : We investigated the correlation between growth efficiency and structural parameters of single-walled carbon nanotube (SWCNT) forests and report the existence of a SWCNT "sweet spot" in the CNT diameter and spacing domain for highly efficient synthesis. Only within this region could SWCNTs be grown efficiently. Through the investigation of the growth rates for ∼340 CNT forests spanning diameters from 1.3 to 8.0 nm and average spacing from 5 to 80 nm, this "sweet spot" was found to exist because highly efficient growth was constrained by several mechanistic boundaries that either hindered the formation or reduced the growth rate of SWCNT forests. Specifically, with increased diameter SWCNTs transitioned to multiwalled CNTs ( multiwall border ), small diameter SWCNTs could only be grown at low growth rates ( low efficiency border ), sparse SWCNTs lacked the requirements to vertically align ( lateral growth border ), and high density catalysts could not be prepared ( high catalyst density border ). As a result, the SWCNTs synthesized within this "sweet spot" possessed a unique set of characteristics vital for the development applications, such as large diameter, long, aligned, defective, and high specific surface area.